Efektivitas Plickers Sebagai Media Evaluasi PPKn Untuk Mengurangi Perilaku Menyontek Siswa SMK Negeri 2 Salatiga - Jessica Sandi Mariana Situmorang; Nani Mediatati (Jayapangus Press, 2023)
Education is a very important and absolute thing for the improvement of human dignity. In education, learning events occur, which whether or not the learning objectives are achieved can be seen through the evaluation process. But in reality, evaluation results sometimes do not match the real abilities of students, because they are obtained through cheating. Therefore, a media innovation such as plickers is needed. This study aims to determine the effectiveness of using plickers as an evaluation media in Civics subjects to reduce cheating behavior of class XI students of SMKN 2 Salatiga. This type of research is descriptive research with data collection techniques using observation, interviews, and documentation. Data analysis techniques used qualitative descriptive techniques. The research subjects were XI DPIB B class with 36 students and XI TAV B class with 35 students. The data sources from each class were two respondents who cheated, and two people who did not cheat. The results showed that there was a reduction in student cheating behavior, from 41.67% to 27.78% in XI DPIB B, and XI TAV B from 55.56% to 28.57%. The effectiveness can be proven through four forms, namely the success of a program, the intended goals / objectives are obtained as a whole, satisfaction with the program, and increased output. The average percentage of these four things is 76.137%, which can be concluded that plickers are effectively used as a Civics evaluation media to reduce cheating behavior of students in class XI SMKN 2 Salatiga.